Keadilan Gender dalam Mewujudkan Keluarga Sakinah Bagi Keluarga Penghafal Al-Qur’an - Musthofa, Mohammad Hendy (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2025)
This study is motivated by the importance of the division of roles between husband and wife with the status of memorizers of the Qur'an, on the one hand serving as parents in guiding and accompanying the family. The purpose of this study was to determine the division of roles according to the concept of gender justice in families of memorizers of the Qur'an. A descriptive qualitative research method was conducted on 5 families to determine the division of roles in the family according to gender. The results of the study indicate that for families of memorizers of the Qur'an, the practice of gender justice is not only normative, but is also applied in everyday life. This is because they make the Qur'an the main guideline in life. How to build a harmonious family by sharing tasks and roles of family members without distinguishing gender and complementing each other. Fair division of roles between family members is an important aspect in building harmonious and Islamic relationships. So that it becomes a harmonious family and in accordance with Islamic values.